Developing Extensive Reading Materials Using Arabic Story Book Based on Bilingual Parallel Text/ ØªØ·ÙˆÙŠØ± Ù…ÙˆØ§Ø¯ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù…ÙˆØ³Ø¹Ø© Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ÙƒØªØ§Ø¨ Ø§Ù„Ù‚ØµØ© Ø¹Ù„Ù‰ Ø£Ø³Ø§Ø³ Ù†Øµ Ù…ØªÙˆØ§Ø² Ø«Ù†Ø§Ø¦ÙŠ Ø§Ù„Ù„ØºØ© - Nasir, Amin; Nafiâ€™ah, Salamatun (Ijaz Arabi Journal of Arabic Learning, 2021)
This research is a research and development on Arabic extensive reading materials using storybooks based on bilingual parallel text. The purposes of this research are to find out the steps in developing Arabic extensive reading materials using storybook based on bilingual parallel text for MA NU Miftahul Falah students and to find out the feasibility of the storybooks and the students responses. This research is a type of research and development. This study uses Richey and Kleins’ model but with some modifications, the stages of this research are: Planning, which is the activity of making a product plan that will be made for a specific purpose. This stage begins with a needs analysis carried out through research and literature study. Production, which is the activity of making products based on the designs that have been made. Evaluation, namely the activity of testing and assessing how high the product has met predetermined specifications. The results of the study, namely the average validity of the storybook that has been developed with all evaluation aspects is 3.49 so it is classified as valid. The evaluation results also show that the product is suitable for use, and the average value of student responses is 84.2 and is in the very good category. Further research needs to be done to determine the effectiveness and efficiency of the product with a wider sample